Tin(IV) Derivatives of N-[o-Hydroxy Substituted (or H) Benzyl] Glycines] - Aman, Robina; Sharma, Reeta; Ballabh Mishra, Shasti; Chandra, Madhup (Asian Journal of Chemistry, 2010)
Several tin(IV) derivatives of N-[o-hydroxy substituted (or H) benzyl] glycines have been prepared by the interaction of tin tetraisopropoxide with the letter in 1 : 1 and 1 : 2 molar ratios in benzene medium. The compounds thus prepared were generally obtained as coloured solids, which were found to be hygroscopic due to the presence of the isopropoxy groups. All these compounds were characterized by azeotrope and elemental analysis. as well as by spectral measurements.